Eco-emotions: validation of the multi-dimensional inventory of climate emotions in an Australian sample - Rice, Kylie; Usher, Kim; Schutte, Nicola S.; Austin, Emma; Patrick, Rebecca; Fatema, Syadani Riyad; Kabir, Humayun; Rock, Adam John; Jones, Rikki; Davies, Ryan L. (Frontiers in Climate, 2025)
IntroductionAustralia’s diverse climate and temperatures render it susceptible to adverse and extreme weather events, and the impacts on social, emotional and psychological wellbeing are complex. Recent studies in Poland, Ireland and Norway validated a multi-dimensional and integrative assessment of the eco-emotions tool, the Inventory of Climate Emotions (ICE).MethodsGiven the extreme variations in geographical, climatic, political and cultural factors experienced worldwide, it is necessary to evaluate the ICE across countries. This study is the first validation of the ICE in an Australian sample (N = 659), and provides evidence of its structure, reliability and validity.ResultsConfirmatory factor analysis indicated a good fit after the removal of one item from the isolation subscale, with model fit indices of CFI = 0.96, TLI = 0.95, SRMR = 0.045, and RMSEA = 0.049. The ICE demonstrated strong internal consistency, with Cronbach’s alphas ranging from 0.79 to 0.94, and moderate test–retest reliability across all subscales except for Powerlessness (ICC = 0.48 to 0.74). Convergent validity was supported by significant positive correlations between ICE subscales and the Hogg Eco-Anxiety Scale, while divergent validity was demonstrated through weak or non-significant correlations with the Riverside Life Satisfaction Scale.DiscussionAs the ICE was not developed in Australia, it may not account for the full range of eco-emotions in the unique ecological and socio-cultural context. However, this study provides important initial support for the use of the ICE in Australia and suggests that some ecological emotions may be common across cultures.